Sistem Pendidikan Tarekat Syattariyah di Nagari Ulakan pada Abad 21 - Adipura Pedro Masela; Ahmad Rivauzi (FONDATIA, 2022)
This study aims to examine the education system of Syattariyah Tarekat in Nagari Ulakan in the 21st century. The method used in this study is qualitative with a phenomenological approach. This research was conducted in Nagari Ulakan. Data was collected by interview, observation, and documentation methods. The data that has been collected is then analyzed by data reduction, data presentation, and drawing conclusions. Validation of the data in this study using triangulation of sources, in which researchers compare data or information obtained in the field and then compare it with books, journals and all references related to the tarekat syattariyah education system. The results of the study show that the Syattariyah tarekat education system in Ulakan is still guided by the Syattariyah council professor in Indonesia, named Sheikh Abdurrauf as-Singkili, in the 21st century. Although in reality, on the ground there are some things that are slightly different from what Sheikh Abdurrauf as-Singkili formulated, this does not become an obstacle or reduce the interest of the Ulakan community to continue to study and adhere to the teachings.